Efficacy and Tolerability of Direct‐Acting Antivirals for Hepatitis C in Older Adults. Issue 7 (25th May 2018) - Mazzarelli, Chiara; Considine, Aisling; Childs, Kate; Carey, Ivana; Manini, Matteo Angelo; Suddle, Abid; Dusheiko, Geoffrey; Agarwal, Kosh; Cannon, Mary D.
Abstract : Objectives: To evaluate the efficacy and tolerability of direct‐acting antiviral (DAA) therapy in individuals aged 65 and older. Design: Retrospective review between June 2014 and January 2017. Setting: Viral hepatitis outpatient clinic. Participants: Individuals aged 65 and older treated with DAA therapy for hepatitis C virus (HCV) during the study period (N=113) divided into 2 cohorts: aged 65 to 74 (n=88) and aged 75 and older (n=25). Measurements: Drug‐drug interactions (DDIs), adverse events (AEs), and rates of sustained virologic response with DAA therapy were assessed. Results: Sustained virologic response rate was 97.7% in individuals aged 65 to 74 and 95.8% in those aged 75 and older. Individuals aged 75 and older were more likely to be taking more than 2 medications per day for chronic conditions (84% vs 62%, p=.02) and more likely to have clinically significant DDIs necessitating cessation or adjustment of medications before commencement of DAA therapy (80% vs 36%, p=.001). Moreover, individuals aged 75 and older were more likely to experience an AE during therapy (50% vs 26%, p=.03) and were more susceptible to developing anemia secondary to ribavirin (60% vs 20%, p=.02). Conclusion: DAA therapy is highly efficacious for the treatment of HCV in older adults, but those aged 75 and older are more likely to have clinically significant pretreatment DDIs and experience AEs, including ribavirin‐induced anemia, during therapy.